PREGNANCY READINESS FOLLOWING WEB-BASED PRECONCEPTION EDUCATION AMONG PROSPECTIVE BRIDES - Winda Agustin; Pipit Sri Estuning; Elies Meilinawati SB (Jurnal Smart Kebidanan, 2026)
Assessing reproductive and pregnancy preparedness among potential brides is crucial for mitigating pregnancy-related risks and enhancing mother and newborn health. This study sought to evaluate alterations in reproductive and pregnancy preparedness subsequent to the implementation of a web-based preconception education program. A quasi-experimental one-group pretest-posttest study was performed using 40 potential brides selected by purposive sampling at the Sidoarjo District Office of Religious Affairs. Participants utilized the web application for a duration of 14 days. Data were gathered utilizing a validated 45-item questionnaire exhibiting exceptional internal consistency (Cronbach’s alpha=0.994) and analyzed employing the Wilcoxon signed-rank test. The median readiness score rose from 98.0 (range: 82–157) at pretest to 183.5 (range: 97–209) at posttest, while the mean score climbed from 107.33±24.27 to 173.25±31.49. A notable disparity was seen between the pretest and posttest scores (Z=−5.181; p<0.001), accompanied by a substantial effect size (r=0.82). The 14-day utilization of the web-based preconception education program correlated with enhanced reproductive and pregnancy preparedness. The program may function as an ancillary teaching resource in premarital services; nevertheless, controlled research are necessary to determine its efficacy.